AB0247 A New Disease Activity Biomarker Alternative To CRP under Tocilizumab Therapy for Rheumatoid Arthritis via Peptidomic Analysis. (15th July 2016) - Seno, T.; Nonaka, D.; Kohno, M.; Sofue, H.; Kasahara, A.; Sagawa, R.; Kida, T.; Kukida, Y.; Fujioka, K.; Fujii, W.; Murakami, K.; Lee, L.-J.; et al.
Abstract : Background: Tocilizumab, anti-IL-6 receptor monoclonal antibody, is widely used for patients with rheumatoid arthritis. IL-6 is essential for production of C-reactive protein (CRP). Tocilizumab fully inhibit the production of CRP. Therefore, we have difficulty in objective assessment of infection and disease activity because the level of CRP is suppressed under tocilizumab therapy. The development of new biomarker alternative to CRP is needed for daily practice. Objectives: To discover new biomarkers alternative to CRP under tocilizumab therapy for rheumatoid arthritis. Methods: We registered patients with rheumatoid arthritis treated with tocilizumab. We collected serum samples from those patients at baseline, 4 weeks after the first tocilizumab administration when patient's CRP level is almost normal, and 1 year later. And we measured CRP, ESR and clinical disease activity index (CDAI) score.Serum peptidomic analysis was conducted by newly-established one-step direct transfer technology (BLOTCHIP-MS analysis), a rapid quantitative technology for peptidomic analysis. All sample measurements were repeated four times. Statistical analyses of MS spectral data were conducted using ClinProTools version 2.2 (Bruker Daltonics). Results: We registered 14 patients and their background is shown in Table 1 . The levels of CRP were 1.16±0.99 mg/dl at baseline, 0.02±0.01 mg/dl at 4 weeks and 0.01±0.01mg/dl at 1 year, respectively. Their CDAI score were 22±9.2 at baseline, 15±8.9 at 4 weeks and 3±2.6 at 1 year, respectively. CRP titer decreased to almost normal level at 4 weeks regardless whether CDAI score did not fully decrease. We detect 6 biomarkers, named as PRSJ01 to PRSJ06, by the peptidomic analysis (Table 2 ). The AUC of diagnostic value of these markers is from 0.742 to 0.858. For example, the level of PRSJ06 significantly decreased 4 weeks (Wilcoxon singed-rank test, p =0.02) and 1 year (Wilcoxon singed-rank test, p =0.003) after first tocilizumab administration (Figure 1 ). and it was inversely-correlated with CDAI score. Conclusions: We detect new disease activity biomarkers alternative to CRP under tocilizumab therapy for rheumatoid arthritis. It is useful for exact evaluation of disease activity and infection during tocilizumab therapy. Disclosure of Interest: None declared